2005
DOI: 10.1007/s00423-004-0528-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of lymph node metastases of papillary thyroid cancer—comparison of the results of histopathology, immunohistochemistry and reverse transcription-polymerase chain reaction—a preliminary report

Abstract: (1) Thyroglobulin (Tg) RT-PCR is an appropriate method of detection for thyroid cancer cells. (2) In combination with histopathology, it might help to qualify patients' nodal status better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Cytological examination of FNA samples was reported to be an accurate method, with high sensitivity and specificity, for detection of metastatic LNs in general head and neck malignancies. [41] The diagnosis of cervical LNs metastases of DTC is often complex because inflammatory lymphadenopathies and nonthyroidal cancer metastases are frequent in this region. [42] Therefore, there are many FP and FN results.…”
Section: Discussionmentioning
confidence: 99%
“…Cytological examination of FNA samples was reported to be an accurate method, with high sensitivity and specificity, for detection of metastatic LNs in general head and neck malignancies. [41] The diagnosis of cervical LNs metastases of DTC is often complex because inflammatory lymphadenopathies and nonthyroidal cancer metastases are frequent in this region. [42] Therefore, there are many FP and FN results.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, routine association of FNAB-Tgp with FNAB-C in the diagnosis of CLN metastasis from papillary and follicular thyroid cancers has been recommended [6,7,15]. Similarly, it has been shown that lymph node detection of Tg mRNA (Tgm) in fine-needle washout implemented the FNAB-C sensitivity for the diagnosis of metastatic CLN from DTC, even if this still needs to be validated on larger case-studies [28]. …”
Section: Introductionmentioning
confidence: 99%
“…In this initial study they reported that Tg detection in fine needle aspirates of non-thyroidal neck masses showed 100% sensitivity in detecting CLN metastasis during the follow-up of patients who were previously treated by total thyroidectomy and 131 I ablation, while FNAC alone showed a sensitivity of 85% [72]. Since then, different studies, measuring Tg protein and/or mRNA, confirmed the utility of Tg determinations in the detection of DTC metastasis in CLN [67][68][69][70][71][73][74][75][76][77][78][79][80][81]. It is worth noting that, differently from serum Tg measurement, Tg detection in the washout of fineneedle aspirates from CLN is not affected by circulating anti-Tg antibodies present in about 20% of patients affected by DTC [82].…”
Section: Molecular Diagnosis In Cervical Lymph Nodesmentioning
confidence: 99%
“…In addition, the same technique may be used to detect calcitonin (CT) protein and/or mRNA for the detection of metastatic medullary thyroid cancer (MTC) [81]. The diagnostic performance of this molecular approach, in terms of sensitivity, specificity, negative and positive predictive value and accuracy was shown to be excellent [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]. Based upon these pieces of evidence, the routine association of Tg protein detection with FNAC in the preoperative diagnosis of suspicious CLN was recommended [17,18].…”
Section: Molecular Diagnosis In Cervical Lymph Nodesmentioning
confidence: 99%